Homologous recombination repair gene mutations in Malaysian prostate cancer patients: Gene mutations in Malaysian prostate cancer - Saeidi, Hamidreza; Raju, Chandramathi Samudi; Ismail, Patimah; Raub, Sayyidi Hamzi Abdul; Omar, Noorjehan; Hisyam Bakrin, ikmal (Cellular and Molecular Biology, 2022)
Genetic alterations in the homologous recombination repair (HRR) genes are associated with an increased risk of prostate cancer development, and patients harboring these mutations can benefit from targeted therapy. The main aim of this study is to identify genetic alterations in HRR genes as a potential target for targeted treatment. In this study, targeted next generation sequencing (NGS) is used to analyze mutations in the protein-coding regions of the 27 genes involved in HRR and mutations in hotspots of 5 cancer-associated genes in four FFPE samples and three blood samples from prostate cancer patients. We identified two mutations in TP53 and KRAS. We also identified four conflicting interpretations of pathogenicity variants in BRCA2, STK11 genes and one variant of uncertain significance in the RAD51B gene. In addition, we detected one drug response variant in TP53, and two novel variants in CDK12 and ATM. Our results revealed some actionable pathogenic and potential pathogenic variants that may be associated with response to the Poly (ADP-ribose) polymerase (PARP) inhibitor treatment. More studies in a larger cohort are needed to evaluate and determine the association of HRR mutations with prostate cancer.